Rol del cuidador en el adulto mayor con discapacidad motora - Argos Martinez, Cristhian Israel (2023)
ABSTRACT: The objective of this research work is to determine the role of the caregiver in the elderly with motor disabilities to establish interventions based on Katharine Kolcaba's theory, which entails analyzing the dimensions of relief, tranquility and transcendence based on the theory of Comfort aimed at caregiver of the adults with motor disabilities in order to meet their needs, the results of the bibliographic review will serve as a source of support for health professionals and caregivers of older adults with motor disabilities. According to the World Health Organization (WHO), disability occurs in various population groups with long-term physical, mental, intellectual or sensory deficiencies that hinder full and effective participation in society or acting on a daily basis on equal terms with others. It is estimated that around 17.2% of the general population a person has some type of disability; It is highlighted that the inclusion of people with disabilities is essential to achieve the Sustainable Development Goals. Bibliographic information was collected from books, guides, scientific journals from indexed medical databases such as: Google academic, Dialnet, Scielo, Scopus, Lilacs, PubMed, ProQuest Elsevier, and several pages were consulted such as: World Health Organization, Pan American Health Organization , Ministry of Public Health of Ecuador, National Institute of Statistics and Censuses. It is concluded that person-centered care for this vulnerable population, covering physical, emotional and social aspects, is of vital importance. Finally, the caregiver role in the elderly with motor disabilities focuses their care, facilitates comfort and helps in the final journey of their lives, the main activities are aimed at ensuring that the person lives the remaining time with the greatest possible comfort.